2021
DOI: 10.2478/cjf-2021-0004
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Invasive Peacock Bass (Cichla Spp.), Its Rapid Distribution and Future Impact on Freshwater Ecosystem in Malaysia

Abstract: Malaysia is recognised among the mega-diversity countries with the abundance of various freshwater species. Malaysian freshwater biodiversity is under threat after the introduction of an invasive peacock bass. The presence of this predator could challenge the coexistence of the native species. In the current review, the most important aspects regarding peacock bass threats to the biodiversity future of local species are addressed. Four non-native species of peacock bass are presently recognised in Malaysia. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 68 publications
(84 reference statements)
0
8
0
Order By: Relevance
“…Although only single sampling location represented the river in the current study, however, most previous studies reported the wild populations of redclaws from the streams and lakes (Idrus et al, 2021;Sallehuddin et al, 2021). Turbid nature (low transparency) of most rivers in Malaysia (Khaleel et al, 2021) could be a possible factor unsuitable for the redclaw to establish in the river habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Although only single sampling location represented the river in the current study, however, most previous studies reported the wild populations of redclaws from the streams and lakes (Idrus et al, 2021;Sallehuddin et al, 2021). Turbid nature (low transparency) of most rivers in Malaysia (Khaleel et al, 2021) could be a possible factor unsuitable for the redclaw to establish in the river habitats.…”
Section: Discussionmentioning
confidence: 99%
“…that have invaded the entire freshwater bodies examined except for Malacca state where only C. temensis existed. Deliberate introductions by local anglers seem to be the main explanation for the expansion of these species in Malaysia [7].…”
Section: Genetic Structurementioning
confidence: 99%
“…Hence, too much angling pressure could be a reason for the number of haplotypes found in Tasik Prima (Selangor), Empangan Timah Tasoh (Perlis) and Tasik Raban (Perak). In Malaysia, Perak and Selangor are hotspot areas for tourist and anglers [7], which may probably increase the chances of Cichla spp. recurrent event of new introduction.…”
Section: Sampling Site Differentiationmentioning
confidence: 99%
See 2 more Smart Citations